1997
DOI: 10.1002/jlb.61.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Differential phosphorylation of the β2 integrin CD11b/CD18 in the plasma and specific granule membranes of neutrophils

Abstract: Abstract:Neutrophil aggregation is mediated by the 132 U1t I fl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In addition to particular kinases regulating L-selectin shedding, phosphorylation levels may be modulated by phosphatases as well. For instance, Buyon et al [54] have demonstrated that granuleassociated phosphatases affect the levels of CD11b/CD18 phosphorylation. Future studies in our laboratory will evaluate the role of phosphatase in influencing the kinetics of L-selectin shedding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to particular kinases regulating L-selectin shedding, phosphorylation levels may be modulated by phosphatases as well. For instance, Buyon et al [54] have demonstrated that granuleassociated phosphatases affect the levels of CD11b/CD18 phosphorylation. Future studies in our laboratory will evaluate the role of phosphatase in influencing the kinetics of L-selectin shedding.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, CD11a is constitutively expressed on PMN surface, whereas other adhesive molecules (CD11b and CD11c) can be taken out from intracellular storage pools situated in 3 mobilizable organelles (specific granules, gelatinase granules, and secretory vesicles). 38,39 We must remember the role played by endocytosis mechanisms in regulating leukocyte adhesiveness. A mechanism of internalization, in fact, has been demonstrated, especially after activation with PMA, for CD18 and CD11b but not for CD11a.…”
Section: Discussionmentioning
confidence: 99%
“…It must be also pointed out that granulocyte activation is accompanied by the integrin phosphorylation 39 that affects only the plasma membrane-associated molecules and not the presynthesized intracytoplasmic reserves; an altered integrin phosphorylation/dephosphorylation balance, related to the PMN spontaneous activation, might explain the decrease of the phenotypical expression of CD11a that cannot be taken back into storage pool.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with our findings in transfected COS-7 cells, these results indicate that the patient's PMN Mac-1, including that translocated from storage compartments, is as effective as wild-type Mac-1 in ligand binding. Studies by Buyon et al 40 indicating that phosphorylation of Mac-1 occurs at the plasma membrane but not in specific granule membranes showed further that chemoattractant stimulation (fMLF) resulted in phosphorylation of only the ␣ M subunit and not the ␤ 2 subunit. This is consistent with our findings of normal activation of the patient's PMN Mac-1 by fMLF stimulation, in that loss of most of the ␤ 2 cytoplasmic domain might be predicted to have no discernible effect under these conditions.…”
Section: Discussionmentioning
confidence: 99%